1997
DOI: 10.1557/jmr.1997.0393
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured high-temperature superconductors: Creation of strong-pinning columnar defects in nanorod/superconductor composites

Abstract: A chemical approach to the formation of columnar defects involving the growth and incorporation of MgO nanorods into high temperature superconductors (HTS's) has been developed. MgO nanorods were incorporated into Bi2Sr2CaCu2Oz, Bi2Sr2Ca2Cu3Oz, and Tl2Ba2Ca2Cu3Oz superconductors at areal densities up to 2 × 1010/cm2. Microstructural analyses of the composites demonstrate that the MgO nanorods create a columnar defect structure in the HTS matrices, form a compositionally sharp interface with the matrix, and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
154
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(157 citation statements)
references
References 45 publications
3
154
0
Order By: Relevance
“…1,3,10,11 Pan et al 1 concluded that the growth of their nanobelts does not take place by the vapor-liquid-solid process which was proposed 18 for the growth of nanowires by a catalyst-assisted technique. 19 Instead, they proposed that the growth was governed by a vapor-solid process, 20 in which the oxide vapor evaporated from the starting oxide directly deposits on a substrate at a lower-temperature region. In our case the source is a compacted disk of oxide which is also the substrate for the micro-and nanostructures.…”
Section: -3mentioning
confidence: 99%
“…1,3,10,11 Pan et al 1 concluded that the growth of their nanobelts does not take place by the vapor-liquid-solid process which was proposed 18 for the growth of nanowires by a catalyst-assisted technique. 19 Instead, they proposed that the growth was governed by a vapor-solid process, 20 in which the oxide vapor evaporated from the starting oxide directly deposits on a substrate at a lower-temperature region. In our case the source is a compacted disk of oxide which is also the substrate for the micro-and nanostructures.…”
Section: -3mentioning
confidence: 99%
“…Nanocrystalline metal oxides have found applications in many technologies including solar energy conversion, [1] ductile ceramics, [2] superconductors, [3] chemical sensors, [4] magnetic devices. [5] Due to their promising perspectives in these myriad areas, many approaches including both physical and chemical strategies have been developed for the preparation of these nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[32] After the nucleation of the wurtzite-structured ZnO nanotetrapods takes place, it appears that the arms of the nanotetrapods reported here prolong via a vapor-solid (VS) mechanism. [36][37][38] This is because no catalyst is used in the growing process, nor are catalyst particles detected at the arm tips. In vapor-liquid-solid (VLS) growth liquid catalyst particles act as the energetically favored sites for absorption of gas-phase reactants and catalyst particles are typically detected at tips of the one-dimensional materials.…”
Section: Resultsmentioning
confidence: 99%